1992
DOI: 10.1136/bjsm.26.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Maximal oxygen uptake in trained and untrained 15-year-old boys.

Abstract: The purpose of this study was to assess maximal aerobic power (VO2max) in trained and untrained 15-year-old boys. The trained subjects (18) were junior swimmers from a Belgrade swimming team, and the untrained ones (12) were from a Belgrade high school. VO2max was directly measured during progressive cycle ergometer exercise using open circuit spirometry. No significant differences in height, mass, percentage fat and vital capacity were noted between the trained and untrained groups. Maximal aerobic power (ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
2
3
0
1
Order By: Relevance
“…Many factors such as age, gender, body position, food intake, body temperature, emotional moments, effect of exercise, environmental factors, etc. have an impact on heart rate (Nicolic and Ilic, 1992).…”
Section: Heart Ratementioning
confidence: 99%
“…Many factors such as age, gender, body position, food intake, body temperature, emotional moments, effect of exercise, environmental factors, etc. have an impact on heart rate (Nicolic and Ilic, 1992).…”
Section: Heart Ratementioning
confidence: 99%
“…Porém, os valores de VO 2max abs, VO 2max rel expresso por kg da MC e VO 2max rel expresso pela massa magra, foram 31,5%, 21,2% e 20,6%, respectivamente, mais altos para os nadadores do que para os escolares (p<0,05). Os autores sugerem que o treinamento físico proporcionou esse aumento significante do VO 2max nos jovens sujeitos 25 .…”
Section: Procedimentos Metodológicosunclassified
“…(1992) with 15-year-old boys, where it was shown that the maximal aerobic power expressed per kilogramme lean body mass was 20.6% higher in the trained than in the untrained group (136). From the similar functional capacity of the fat free mass for subjects with a solid, average or slender body build in this study, suggests a similar physical exercise level in the groups.…”
Section: Discussionsupporting
confidence: 57%